Industrial tribology sustainable machinery and industry 4.0 - Katiyar, Jitendra Kumar; Ruggiero, Alessandro G.; Rao, T. V. V. L. N.; Davim, J. Paulo 1964- (CRC Press, 2023)
"Covering energy saving technologies and how these are incorporated into component design, the book is relevant to industries including automotive engineering, and discusses the topical issue of sustainability in industry This book details recent fundamental developments in the field of tribology in industrial systems. Tribology has advanced significantly in recent years. Tribological performance depends on external parameters such as contact pressure at interface, system temperature, relative speed between bodies and contact behaviour. Through ensuring that mechanisms work in an energy efficient manner, minimising wear, engineers need to implement the study of tribology to improve the life of machinery within industry. Essential to the study of component design and condition monitoring, the book touches upon topics such as gears, bearings and clutches. Additionally, it discusses tribology's relation to Industry 4.0, and incorporates the results from cutting edge research. Industrial Tribology will be of interest to all engineers working in industry, involved in mechanical engineering, material engineering, mechanisms and component design and automotive engineering"--...
Includes bibliographical references and index
Keywords: Tribology; Industry 4.0